آليات تشكيل مجالس وحدات الادارة المحلية, ودورها في التنمية المحلية - الحسين محمد; اسماعيل شادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يقتضي تحقيق الإدارة المحلية للغاية المرجوة منها, توخي الدقة في اختيار العناصر التي يوكل إليها العمل في الوحدات المحلية, الأمر الذي يقتضي أن تكون تلك العناصر من المتفهمين للواقع المحلي, والمتمتعين بالخبرة الفنية الكافية, وفي إطار عجز الأسلوب المتبع في تشكيل المجالس المحلية عن تحقيق اهداف الادارة المحلية كافة, يختلف الفقه والتشريع في تحديد الأسلوب الواجب اتباعه في إطار أولوية تلك الأهداف, وفي إطار الواقع السياسي, الاقتصادي والاجتماعي السائدة في كل بلد, حيث تتجه بعض الأنظمة لاعتماد الانتخاب في اختيار أعضاء المجالس المحلية, في حين يتجه البعض الآخر لاعتماد أسلوب التعيين أو الجمع بين أسلوبي الاختيار والتعيين بغرض الاستفادة من مزايا الأسلوبين, ويبقى حاجة ورغبة النظام القانوني السائد والإمكانات المتوافرة هي التي تحدد الأسلوب الواجب اعتماده. Achieving the intended purpose of the local administration requires carful selection of the elements assigned to work in local units, which requires that those elements are aware of local reality and have sufficient technical expertise. In the context of the inability of the method used in forming local councils to achieve the objectives of local administration, the jurisprudence and legislation differ in determining the method to be followed within the priority of those objectives and within the political، economic ،and social reality in each country. Where some systems tend to adopt the election in selecting the members of local councils , while others tend to adopt the method of appointing or the combination of (election and appointing) methods in order to take the advantages of both methods . But, it is the need and desire of prevailing legal system and the possibilities available , that determine the method to be adopted